Social Class Inequality in 1912 English Society as Reflected in J.B. Priestley's Play Script An Inspector Calls - Yahya, Wirda Humaira; Mansyur, Agus Salim; Pramita, Agry (Vivid: Journal of Language and Literature, 2025)
This study examines social class inequality in 1912 English society as reflected in J.B. Priestley’s play An Inspector Calls. The play highlights the structure of society based on powerful class differences, where the upper class represented by the Birling family and Gerald Croft have privileges that the working class represented by Eva Smith does not have. The study uses a mimetic approach that views literature as a reflection of human life. To explore how inequality is portrayed through interactions between characters, this study uses a qualitative descriptive method. In addition, it uses the concept of base and superstructure in Marxism to examine how the economic structure (base) shapes and maintains social norms, ideologies, and institutions (superstructure) to perpetuate the dominance of the bourgeoisie over the working class. The results of this study reveal three main aspects: labor exploitation, class domination and social control, and gender inequality in capitalism. The results show that An Inspector Calls not only serves as a play, but also as a critique of capitalist society, by exposing how the economic structure maintains class-based oppression.